The Effect of Bentonite Activation and Its Application on Reducing Metal Ions Levels in Wastewater - Estiarny, Resfy Ella; Agustina, Tuty Emilia; Sari, Tuti Indah; Gayatri, Rianyza (Jurnal Teknologi, 2025)
Heavy metal pollution such as Cu²⁺, Fe³⁺, and Pb²⁺ metal ions resulting from industrial and laboratory activities has become a serious environmental issue due to their toxic and bio-accumulative nature. This study aims to evaluate the adsorption effectiveness of natural bentonite and bentonite activated chemically with H₂SO₄ followed by thermal treatment at 300 °C. The activation process was intended to enhance surface area, porosity, and the number of active sites on the bentonite surface. Adsorption experiments were conducted using synthetic wastewater containing Cu, Fe, and Pb metal ions with varying adsorbent masses (1–5 grams), and surface morphology characterization was performed using SEM-EDX. Results showed that acid-thermal activated bentonite had a more porous and fragmented surface structure compared to natural bentonite, contributing to higher adsorption efficiency. At an adsorbent mass of 5 g, Pb removal reached 92.5% with acid-thermal activated bentonite, whereas natural bentonite achieved only 85.5%. Additionally, the removal efficiency of Fe³⁺ and Cu²⁺ ions also significantly increased after activation. These findings indicate that chemical and thermal activation synergistically enhance the performance of bentonite as an effective adsorbent for treating hazardous wastewater containing heavy metals.